The Impact of Changes in Land Use on Green Open Space and Comfort Index in Semarang City, Indonesia - Penggayuh, Dinda; Munibah, Khursatul; Ardiansyah, Muhammad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Semarang City is one of the cities with the most dense population in Indonesia. The increase in the population of Semarang City causes land conversion which has an impact on increasing heat and can cause environmental problems. The results of the random classification of forests for land use in 2013-2022 are dominated by the built-up land class. Use of built-up land continues to increase from 2013-2022 by 8.84% or an area of 3410 ha. This causes a reduction in green open space by 7.59% or an area of 2928.49 Ha and is still sufficient by 30%. In the predicted use of land in 2032, the dominance of the built-up land class is 61% (23,575 ha). The availability of green open space (RTH) in Semarang City continues to decline from 2013-2032 by 9%. Where in 2032 the availability of green open space will be 29.62% or less than 30%. The relationship between green open space and comfort levels influences each other, where a reduction in green open space causes an increase in comfort levels. Directions need to be made for developing green open spaces consisting of priority 1 areas, namely adding green open spaces in each sub-district, maintaining existing green open spaces, and creating roof gardens and vertical gardens to reduce temperatures in densely populated areas. Meanwhile, priority area 2 is maintaining existing green open space in the form of urban forests and plantation areas.